Coaching the quiet: Exploring coaches' beliefs about shy children in a sport context. (March 2020) - Kirkpatrick, Alison; Rose-Krasnor, Linda; Ooi, Laura L.; Coplan, Robert J.
Abstract: Organized sports may enhance the social skills and peer relationships of shy children. Interactions with coaches may be critical determinants of these benefits. Thus, our goal was to explore coaches' beliefs, attitudes, and responses to shy children. Participants were 447 undergraduate students (343 female; M age  = 19.39 years, SD  = 2.12) with coaching experience. Participants indicated their anticipated behaviours, emotions, and perceived implications in response to hypothetical children exhibiting shy, unsociable, and verbally exuberant behaviours in a sport context. Coaches viewed shy behaviour more problematically than both verbally exuberant and unsociable behaviours, anticipating the most negative implications for shy children's peer relationships, development, and team performance and supporting the use of differential coaching strategies. However, despite reporting the most worry about shyness, coaches were less likely to intervene in response to shyness compared to exuberance. We discuss the implications that our results may have for the adjustment of shy children. Highlights: Coaches can differentiate between different types of social withdrawal in children. Coaches view shy behaviour as more problematic than unsociable or verbally exuberant behaviour in a sport context. Coaches anticipate the most negative social and developmental implications for shy children. Coaches respond with different strategies to different social behaviours. Coaches report the most worry in response to shy behaviour but are less likely to intervene in response to shyness.